DESCRIPTION OF THE SUITABILITY OF CONTRACEPTION SELECTION BY FP ACCEPTORS AT MANIS JAYA HEALTH CENTER, TANGERANG CITY, 2023 - Elsera, Golda; Sutarno, Maryati (HEARTY, 2024)
Background : Efforts to create quality families, the main target is to control population growth and increase quality small families as indicated by the increase in rational, effective and efficient contraceptive methods, namely the use of long-term contraceptive methods (MKJP). Purpose of writing : To determine the appropriateness of contraceptive selection by family planning acceptors at the Manis Jaya Community Health Center, Tangerang City in 2023. Research Method : Primary data was collected using a questionnaire. The research method uses a cross sectional type of research with a quantitative approach. The independent variables are age, family support, number of children and fear of side effects and the role of health workers. The dependent variable is the appropriateness of contraceptive selection. The data analysis used was univariate and bivariate analysis using the chi square test. Research Results: Based on the research results, there is a significant relationship between the age of family planning acceptors, family support, number of children and the role of health workers and the appropriateness of contraceptive selection at the Manis Jaya Community Health Center, Tangerang City in 2023. There is no significant relationship between fear and the role of health workers and suitability of contraceptive selection at the Manis Jaya Community Health Center, Tangerang City in 2023. Conclusions and Suggestions : It is hoped that all health workers will provide knowledge by providing education about family planning contraception so that prospective family planning acceptors are correct in choosing family planning contraception.